Taboo Revisited in Dystopia: Aldous Huxley's Brave New World - Arikan, Seda (Johns Hopkins Univ Press, 2025)
This article reads Aldous Huxley's dystopian novel Brave New World as a portrayal of two societies, one primitive and the other futuristic, founded on taboos. Although the two contradictory worlds survive on opposite taboos, the study argues that the social and psychic mechanisms behind the operation of taboos in the Savage Reservation and in the World State are structurally similar. Drawing on Sigmund Freud, Jacques Lacan, Slavoj & Zcaron;i & zcaron;ek, and Julia Kristeva, the article examines Huxley's narrative of taboos in terms of the dialectic of desire and law.